The Images of Happiness on Native Youth West Kalimantan - Rizal, Yenni; Lestari, Melina (International Journal of Research in Counseling and Education, 2024)
The aim of this study was to find out the images of happiness on native youth of West Kalimantan along with the components of happiness which are consists of affective and cognitive aspects. The research method of this study was quantitative which involving 377 participants consisting of 3 native groups; Malay , Dayak and Chinese. Happiness instruments concept adapted from Satisfaction with Life Scale (SWLS), instrument scaling through calibration and standardization by using Rasch Models.The study found out the images of happiness on native youth of West Kalimantan, namely; for 2 ethnic with the level of happy being in youth Malay and Chinese . Whereas the Dayak youth is only at sufficient level or could be interpreted it has the lowest level compared to 2 other ethnic.